Arterial Stiffness Use for Early Monitoring of Cardiovascular Adverse Events due to Anthracycline Chemotherapy in Breast Cancer Patients. A Pilot Study - Souza,Cláudio Antônio de (2018)
Abstract Background: Chemotherapy with doxorubicin and cyclophosphamide, although efficient for treating breast cancer, is associated with cardiovascular complications. Recent studies seek to identify methods that can early detect cardiological and vascular changes as a strategy to decrease the incidence of cardiovascular comorbidities. Objective: To evaluate the role of arterial stiffness measurement in the monitoring of doxorubicin and cyclophosphamide-induced cardiotoxicity in breast cancer patients. Methods: Prospective longitudinal study in 24 breast cancer patients undergoing treatment with doxorubicin and cyclophosphamide. Patients underwent an indirect evaluation of arterial stiffness through non-invasive measurement of hemodynamic parameters such as pulse wave velocity with the Mobil-O-Graph® 24H PWA device at three different times of the chemotherapy treatment (pre-chemotherapy, after the first and the fourth cycle). The left ventricular ejection fraction was also evaluated by Doppler echocardiography (pre-chemotherapy and after the fourth chemotherapy cycle). Data were considered significant when p ≤ 0.05. Results: Patients had a mean age of 52.33 ± 8.85 years and body mass index of 31 ± 5.87 kg/m2. There was no significant difference between the hemodynamic parameters evaluated by the oscillometric method or in the left ventricular ejection fraction in the different evaluated periods. Conclusion: Evaluations of arterial stiffness by oscillometry and measurement of left ventricular ejection fraction by Doppler echocardiography showed equivalence in the values found, suggesting that the evaluation method of arterial stiffness studied could be used as a marker for cardiovascular adverse events associated with doxorrubicin-based chemotherapy drugs.